Leader Effects and Gender Differences in Sequential Restaurant Ordering Environments. (15th November 2018) - Schamel, Guenter; Santos-Arteaga, Francisco Javier
Abstract: We empirically examine the strategic importance of the choices of the first person ordering, that is, the leader, for the decisions made and money spent by other commensals at a restaurant table. Our aim is to study the similarity of orders—in terms of dishes, drinks, and prices—among the table leader and the other commensals. The empirical results reveal that table leaders, both male and female, exert a considerable influence on the choices made by other diners. We analyze the differences arising when males and females act as table leaders. (JEL Classifications: D12, D91)